Lace = Blutsbande <engl.> - Conran, Shirley (London : Book Club Associates, 1982)
"Which one of you bitches is my mother?" Four elegant, successful, and sophisticated women in their forties are called to New York's Pierre Hotel to meet Lili -- a beautiful, young, and notoriously temperamental Hollywood movie star. None of the women knows exactly why she is there; each has a reason to hate Lili and each of them is astonished to see the others. They are old friends who share a guilty secret and who have for years been doing their best to keep that secret quiet. Their lives are changed forever, however, when Lili suddenly confronts them. When the women refuse to answer her, Lili proceeds to travel around the world through the playgrounds of the rich and famous, seeking to answer the question that has obsessed and almost destroyed her. From Paris to London, from the boardroom to the bedroom, Lace takes the reader into the rarified world of five unforgettable women who are as beautiful, as complex and as strong as.lace.
Zweigstelle: Patientenbücherei Psychiatrie
Exemplar/Standort: Engl Conr (PatBü Psych)
Exemplar/Standort: Patientenbücherei Psychiatrie
Text in engl. Sprache
Keywords: Englisch; Fremdsprachiger Text